Cover Feature: Lithium Dependent Electrochemistry of p‐Type Nanocrystalline CuCrO2 Films (ChemElectroChem 23/2022). Issue 23 (11th November 2022) - Chown, Amanda L.; Yeasmin, Humaira; Paudel, Rajendra; Comes, Ryan B.; Farnum, Byron H.
Abstract : The Cover Feature illustrates lithium‐coupled redox reactions between Cu 2+ and Cu + at the surface of CuCrO2 delafossite nanocrystals. The lithium‐coupled redox activity is the result of copper vacancy defects at the nanocrystal surface where Li‐ions occupy vacant sites in the reduced state and return to solution in the oxidized state. CuCrO2 nanocrystals are used as hole transport materials in a wide array of solar cell technologies where the existence and reactivity of these surface defects can have wide ranging effects on solar cell performance. More information can be found in the Research Article by A. L. Chown et al .